Structural change in forward contracting costs for Kansas wheat - Taylor, Mykel R.; Tonsor, Glynn T.; Dhuyvetter, Kevin (My University, 2015)
Farmers use forward contracts to eliminate adverse price and basis movements prior to harvest. Since late 2007, the local basis for Kansas wheat has changed dramatically relative to historic levels, causing greater risk exposure for elevators o ffering forward contracts. The result has been an increase in the cost of forward contracting paid by farmers from $0.086 per bushel to $0.327 per bushel. The factors driving this increase in costs are basis volatility, wheat futures harvest price, the information available in the market as harvest approaches, and realized returns to the elevator from forward contracting in previous years.
Keywords: Basis; Convergence; Forward contract; Kansas wheat; Risk; Volatility